A distance in-service teacher education setting focused on mathematics investigations: The role of reflection and collaboration - Ponte, João Pedro da (2011)
This paper discusses how several teachers were involved in a distance in-service course inspired by the notion of teachers’ inquiry. The participants are middle and secondary school teachers who register and work with a partner. We provide case studies of three groups of teachers, tracing their professional development concerning mathematical investigations, reflection and collaboration practices. The three cases show strikingly different experiences. Some teachers adjusted well to the format and activities proposed but others had trouble in assuming an active role. We conclude that reading, discussing, doing open-ended tasks, reflecting and collaborating are powerful activities but require a specific readiness.